A Systematic-Integrative Model of Case Study and Case Analysis Methods in Developing Students' Decision-Making Competence (MMIT Proceedings, 2026)
This article analyzes the need to develop students' strategic thinking, critical analysis, and informed decision-making skills in the modern education system. During the study, the purpose, nature, function, and results of the Case Study and Case Analysis methods were analyzed on the basis of a systematic approach, and their integrative model was developed. The proposed model serves to develop students' cognitive competencies by linking the stages of problem study, analysis, and selection of the optimal solution. The results of the study show that the integrative use of these methods has high pedagogical effectiveness.
Keywords: decision-making competence; Case Study; Case Analysis; systematic approach; cognitive competence; critical thinking; strategic thinking; pedagogical technologies; higher education; problem situations; soft skills; integrative model